Association of alirocumab therapy with inflammatory lesions of the vocal folds: A case report. (9th December 2016) - Benedict, Peter A.; Abdou, Rania M.; Dion, Gregory R.; Woo, Peak; Branski, Ryan C.; Amin, Milan R.
Abstract : Therapeutic monocolonal antibodies (MAbs) are a new, rapidly growing class of medications that frequently have poorly characterized side‐effect profiles. We present a patient who developed inflammatory lesions of the vocal folds in temporal relation to the initiation of alirocumab. Lesions of the vocal folds represent a previously unreported adverse effect of alirocumab therapy, making it the second MAb documented with such a side effect. The potential laryngeal effects of alirocumab specifically, and of MAbs more broadly, warrant investigation. Laryngoscope, 127:1652–1654, 2017